Enzyme Immobilization Technology in Biofuel Production: A Review. Issue 1 (February 2021) - Shamsudin, M I; Tan, L S; Tsuji, T
Abstract: The application of enzymes as biocatalyst is well recognized in the field of green engineering. Due to their outstanding properties such as inconsumable in chemical reaction, highly specific in action, and speeding up the reaction rate, they are widely used in the conversion of various renewable sources into biofuel. Biofuel, in recent years, had shown such great potential in becoming the alternative for the petrol-derived fuel since it is generated from biomass origins. Researchers currently had introduced few enzyme modifications such as gene editing and supercritical fluid extraction techniques in order to maximize their catalytic performances. However, all of those methods are more tedious and still lack in maintaining the regenerative ability of the enzymes as well as their stabilities. Hence, the technique of enzyme immobilization is currently applied in the biofuel production in improving the enzymes' performances by providing extra physical support known as backbone to the enzyme to speed up the reaction. Thus, this review aims to provide better insight on the current immobilization technology as well as the enzyme immobilization itself in biofuel generation. Different types of biofuel produced in the industry is also reviewed. The working principles, mechanisms, characteristics, and advantages of the enzyme immobilization technique is also conferred. Besides, comparisons between mobilized, extracellular immobilized and intracellular immobilization will also be reviewed along with the types of matrices used in the adsorption immobilization methods. Lastly, some issues regarding this technique are also highlighted in improving the enzyme performance itself.